Knowledge and Preparedness Regarding Chemical, Biological, Radiological and Nuclear (CBRN) Warfare among Doctors and Medical Students at Combined Military Hospital (CMH) Lahore Medical College : Chemical, Biological, Radiological and Nuclear (CBRN) Warfare among Doctors and Medical Students - Rahman, Fariha; Shakoor, Fatima; Raza, Tahira; Sher, Gull; Aziz, Bushra (Pakistan Journal of Health Sciences, 2024)
Chemical, biological, radiological and nuclear-related disasters have become increasingly common all around the world. Objectives: To assess the knowledge and preparedness regarding chemical, biological, radiological and nuclear Warfare among Doctors and Medical students at Combined Military Hospital Lahore Medical College. Methods: In this descriptive cross-sectional study, 311 respondents participated from November 2022 to May 2023. Non-probability convenience sampling technique was used. Data were analyzed on SPSS version 26.0. Results: The study revealed a significant knowledge gap regarding chemical, biological, radiological and nuclear warfare. Almost 290 participants had never encountered the term 'chemical, biological, radiological and nuclear' signifying a substantial lack of awareness. Furthermore, a slightly higher knowledge gap was observed among female participants, although this difference did not reach statistical significance (p-value=0.07). Additionally, students in their 3rd, 4th, and final years of medical college demonstrated a more comprehensive understanding of chemical, biological, radiological and nuclear compared to those in their initial years of study (p-value=0.008). Conclusions: It was concluded that there is a significant knowledge gap about chemical, biological, radiological and nuclear Warfare and its management among medical professionals. A very low percentage of professionals were properly trained in chemical, biological, radiological and nuclear emergency management. Respondents stressed the inclusion of chemical, biological, radiological and nuclear emergency management training in the curriculum. These findings suggest that proper provision of knowledge, and training related to these disasters is inevitable for timely management and future risk reduction from such events.